Recent Biochemical Markers for Cardiovascular Diseases: Diagnostic and Prognostic Implications - Dalal, Deepika; Malik, Ashish Kumar; Dhama, Anjali; Ghalaut, Veena Singh (Current Practice in Medical Science Vol. 11, 2022)
Cardiovascular diseases are the leading cause of mortality and morbidity worldwide. Early identification of a potential CVD risk and early intervention can contribute to a better prognosis. Cardiac biomarkers are very important in the early diagnosis in golden period so that early intervention can be done and possibly myocardial damage can be reversed. Various studies have highlighted the potential biochemical markers associated with cardiac tissue, inflammation and underlying metabolic processes that may aid in the clinical assessment of the vulnerable or high-risk population. This chapter provides an overview of cardiac biomarkers being widely used as diagnostic and prognostic tools for CVD risk assessment.